ALGORITMA K-MEDOIDS UNTUK MENENTUKAN CLUSTERING DATA COVID 19 DI DKI JAKARTA - Samudi, Samudi; Widodo, Slamet; Brawijaya, Herlambang (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Technology currently plays a very important role in supporting all information circulating in the community, various things such as conveying information about a developing covid 19 virus, Covid 19 data sets which can currently be opened in open data owned by the DKI provincial government. Jakarta is very helpful for researchers to examine the development of this information. From the available data, the researchers took research on grouping Covid data from data treated, died, self-isolated, and recovered, from a data set of about 28,036 we processed it into 267 testing data. With the K-Medoids Algorithm, researchers conducted research that would be made into several clusters, because this algorithm can approach an object in conducting research. The results of this study were obtained into 3 clusters with 85 items in the zero cluster, 123 items in the first cluster, and 59 items in cluster 2. It can be seen that the results of the study for the healing rate of COVID patients are very much improved which is depicted in the centroid plot view.